If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 8 = -4(x + 7) Reorder the terms: 8 + y = -4(x + 7) Reorder the terms: 8 + y = -4(7 + x) 8 + y = (7 * -4 + x * -4) 8 + y = (-28 + -4x) Solving 8 + y = -28 + -4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + y = -28 + -8 + -4x Combine like terms: 8 + -8 = 0 0 + y = -28 + -8 + -4x y = -28 + -8 + -4x Combine like terms: -28 + -8 = -36 y = -36 + -4x Simplifying y = -36 + -4x
| y=(x)2-2 | | 3(4y-3)=7 | | h(t)=150t-5t | | 4-6(x-4)=2(x-4) | | 8x-92=5x-8 | | 2(-5a^2+8a-12)-(a^2-3a-7)= | | 3-(8x+6)=3 | | 0x-3=0 | | 0y-3=0 | | 4x-8-3(x-5)=3(x-1) | | y-15=32 | | -11nk^2+5nk-6y=0 | | 2[1-3(x+2)]=-x | | 54-4x=14x+22 | | 2d-17=3d+8 | | 3(y+7)+4=43 | | 142-7x=20x+22 | | q+3q=2q-6 | | x+1=-15 | | -4r+5=-3r+9 | | 3(-8x)+8=80 | | 3z-3(1-z)=z-17 | | -8h-1=-33 | | 9(y-4)-3y=6(y-6) | | 90+4x+x=180 | | 15=-2p+27 | | -6(-x-10)=10(-x-10) | | 8x-9x=73-82 | | 0.50x+0.15(70)=48.5 | | 35+x=18 | | -7(3a+10)=0 | | 4(w+1)=6-2(1-2w) |